Impact of the COVID-19 Pandemic on the Academic Performance of Undergraduate Students at Pokhara University - Thapa, Ajay (Journal of Development and Social Engineering, 2023)
The disruption in the lives of students around the globe due to the COVID-19 pandemic has been considered the largest disruption in the history of formal education. Schools and Universities were closed for several months almost everywhere around the globe. The students of Nepalese universities were also affected by this pandemic. In this context, using the data enumerated from 89 undergraduate students studying at undergraduate programs in the School of Development and Social Engineering, Pokhara University by means of an online survey, this study has explored the means of accessing online classes and assessed the impact of the COVID-19 pandemic on the academic performance of undergraduate students. This study revealed that the Zoom platform, smartphones and tablets, Wi-Fi, and electricity were the major means to attend online classes. Despite many negative effects of the pandemic on different aspects of life, the COVID-19 pandemic has had a positive impact on their academic performance. However, the study did not find significant gender and rural-urban differences in the impact of the pandemic on the academic performance of students.